Atom Probe Tomography on Semiconductor Devices. Issue 12 (6th April 2016) - Khan, Mansoor Ali; Ringer, Simon P.; Zheng, Rongkun
Abstract : In this paper, state‐of‐the‐art Atom Probe Tomography (APT) on industrial semiconductor products is reviewed to explore their device physics and to develop an understanding of atomic‐scale interfaces in them. Different semiconductor devices, such as Light Emitting Diodes (LEDs), High‐Electron‐Mobility Transistors (HEMTs), Field‐Effect Transistors (FETs), Metal‐Oxide‐Semiconductor Field‐Effect Transistors (MOSFETs), Static or Dynamic Random Access Memory (SRAM or DRAM) and solar cells, have been reviewed in light of their surface morphologies, chemical compositions, dopant distributions, grain boundaries and interface characteristics. The APT approach allows for the further optimization of device techniques, which are suggested for better performance. Abstract : In this review the recent progress in the atomic‐scale tomography of various semiconductor devices by atom probe tomography is summarized and evaluated. It demonstrates the unique capability of atom probe tomography in device analysis and optimization, and can serve as a guidance and reference for scientists and engineers in the relevant fields.